Telemedicine: Advancing Smarter by Evolution through Decades - Imran, Mohd (Asian Journal of Pharmaceutics (AJP), 2024)
Telemedicine has undergone significant transformation over the past several decades, evolving from rudimentary communication tools to sophisticated digital health platforms. This manuscript examines the historical progression, technological advancements, and broad applications of telemedicine, highlighting its impact on health-care delivery. A systematic review of literature and case studies was conducted, focusing on the technological, regulatory, and clinical aspects of telemedicine. Key sources include peer-reviewed journals, official health organization reports, and case studies demonstrating practical applications of telemedicine. The evolution of telemedicine is closely linked with advancements in communication technologies, including the Internet, mobile devices, and artificial intelligence. These technologies have enhanced the accessibility, reliability, and functionality of telemedicine platforms. Telemedicine has significantly improved health-care delivery, particularly in remote and underserved areas. It has enabled remote consultations, diagnostics, chronic disease management, and mental health services, thus increasing patient access and continuity of care. Telemedicine represents a transformative shift in health-care delivery, offering enhanced patient care, improved access, and cost efficiencies. Its evolution reflects continuous innovation, increased acceptance, and supportive regulatory environments. Future efforts should focus on overcoming existing challenges and leveraging emerging technologies to further integrate telemedicine into the health-care ecosystem. The potential applications of telemedicine extend beyond traditional health-care settings, promising smarter, more efficient, and more equitable health care for all